PROBLEMS FACED BY THE NEWLY APPOINTED PUBLIC SECONDARY SCHOOL TEACHERS: A CASE STUDY IN DISTRICT FAISALABAD - Umar Farooq; Dr. Ghazanfar Ali Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Education plays a vital role in the progress of any nation. Education developed and improved the persons individually, intellectually, mentally and socially. It is much difficult for newly appointed teachers to adjust with sudden and unexpected changes in a short time. In the new era of education, young teachers have high quality of characteristics, high percentage of marks, high imagination, and passion for standard work. New comers face many problems in any field of life. Like other fields of life, newly appointed teachers also face many problems and difficulties in the starting of their new profession. Aim of this research is to examine the problems faced by the newly appointed public secondary school teachers in district Faisalabad. The present study was conducted in district Faisalabad. The population of this study consisted of 121 newly appointed public secondary school teachers (2017 and 2018) in district Faisalabad. The sample size 92 had been calculated through www.surveysystem.com by keeping confidence level 95% and confidence interval 5%. Data were collected through questionnaire. Simple random sampling technique was used to collect data from the respondents. Statistical Package for Social Sciences (SPSS) was used to analyze the collected data. Regarding “problems faced by the teachers during recruiting” as lack of communication and interaction among students and teachers was ranked on 1st position with mean value 3.55. Regarding “problems in classroom management faced by the teachers” as improving learning outcomes was ranked on 2nd position with mean value 3.46. According to “difficulties faced by the teachers” as over burden was ranked on 3rd position with mean value 3.37. With reference to “factors that effects the teaching learning process” as time management was ranked on 4th position with mean value 3.34. According to the ranking, on the 5th position, the respondents said about that “communication gap” and it is tending towards to sometime with mean value 3.1. After the research study in which opinion were taken from many members. According to their opinions they had to face many difficulties like as lack of authorities’ assistance, lack of modern assets, lack of parent association and the trouble of adjusting their showing and their own survives. Some major challenges such as continuity of professional programs, the high cost of training among others which inhabit the whole teacher’s professional development.